PERAN PENGAJIAN TERHADAP PERKEMBANGAN KONSEP KEBERAGAMAAN PADA DIRI REMAJA DI KOTA BANJARMASIN - Armiah Najla (UIN Antasari Banjarmasin, 2017)
Religious, for adults is a way of life and not just follow-up. But what about teenagers? Many psychologists say teens are investigating religion as a source of emotional and intellectual stimulation. Teens do not want to take for granted the religious material he hears. Teenagers will cultivate and then decide. In this process comes the significant roles of others who will direct the concept of religiousness in adolescents. Researchers want to see how the influence of reference groups and the environment in shaping and developing adolescent self-concept especially in adolescent religiousness.